Dual Triumphalist Heritage Narrative And The Sungai Buloh Leprosy Settlement - Por, Heong Hong (Palgrave Macmillan, 2020)
Unlike other heritage movements in Malaysia, which are largely ethnicbased and culture obsessed (Cartier 1996; Worden 2001), the preservation movement of the Sungai Bulah Leprosy Settlement (SBLS thereafter), also widely referred to as the "Valley of Hope", 1 is concerned with the conservation of a site that is associated with a socially stigmatised disease. Built at a jungle fringe in Selangor in 1930, SBLS was constructed as a place for the treatment, and forced isolation from wider society, of people suffering from leprosy. Although leprosy knows no racial boundaries as people of any background can be afflicted with the disease, nearly eighty per cent of the patients admitted to SBLS have been ethnic Chinese. Of the rest, about fifteen per cent were ethnic Malays with ethnic Indians making up five per cent. Former patients who were cured but left with differing degrees of disfigurement and disability are also residents of the SBLS today.2 SBLS's population reached its peal<. with 2400 people in 1958, but today their number is just slightly over one hundred (JoshuaRaghavar 1983; Wong and Phang 2006).